Is leg-to-leg BIA valid for predicting minimum weight in wrestlers? - Clark, R. R.; Bartok, C.; Sullivan, J. C.; Schoeller, D. A. (Medicine & Science in Sports & Exercise, 2005)
Background: The National Collegiate Athletic Association (NCAA) and several state associations require prediction of minimum weight (MW) for collegiate and high school wrestlers. The rule requires assessment of body composition before the competitive season to minimize unhealthy weight-loss practices. Leg-to-leg bioelectrical impedance analysis (BIA) has been suggested for use with wrestlers.